Quality evaluation of developed herbal high protein biscuits by incorporating trikatu and soya bean - Hasker, E; Sri, S Radhai (Journal of Postharvest Technology, 2020)
Biscuits are the most popular snack foods with high energy density and extended shelf life. Herbs like pepper, long pepper and ginger  are medicinally and nutritionally important as they contain some active components which are considered to be helpful for leading a  healthy life. Current study is an effort to incorporate these herbs in biscuits and to study its quality parameters. Soya bean is also added  to improve the protein content of the biscuits. In Ayurveda the term Trikatu is used as a combination of natural herbs. It is a combination  of Black Pepper (Piper nigrum), Indian Long Pepper (Piper longum) and Ginger (Zingiber officinale). Powdered spices of black pepper,  dry ginger and long pepper were mixed and incorporated in wheat flour in 1,2,3,4,5,6,7,8,9,10,11,12 and 13 percentages for biscuit  production. Analysis of wheat flour for various physico –chemical parameters were carried out. Textural properties of the flour were  performed by Farinograph and Extensograph. Herbal high protein biscuits were prepared with incorporation of soya bean flour by  replacing the flour by 3,4,5,6,7,8,9,10,11,12,13,14 and 15 percentages .The prepared biscuits were analyzed for physical, chemical and  sensory analysis.
Keywords: Biscuits; herbs,; protein; flour,; quality; sensory analysis